2017
DOI: 10.15171/jnp.2017.50
|View full text |Cite
|
Sign up to set email alerts
|

Renal failure in cancer patients: results from the national cancer registry of Abidjan, Côte d’Ivoire

Abstract: Background: Renal failure (RF) is a risk factor for morbidity and mortality in cancer patients. Objectives: To describe the profile of cancer patients with RF. Patients and Methods: This is a retrospective descriptive study of RF in patients enrolled in the national cancer registry of Abidjan, during the period from January 2012 to December 2015. The diagnosis of RF was confirmed based on a measured glomerular filtration rate (GFR) < 60 mL/min obtained using the Modification in Diet of Renal Disease (MDRD) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Glomerular filtration rate with Modification of Diet in Renal Disease was found to be <90ml/min in breast cancer 67.8%, colorectal cancer 59.5%, lung cancer 52.6% prostate cancer 62.6% and gynecologic cancer 69.6%. In the study by Yao et al, renal failure rates in cancer patients were found to be 38.2% in uterine cancer, 10.2% in breast cancer, 9.2% in prostate cancer, and 7.2% in liver cancer (16).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Glomerular filtration rate with Modification of Diet in Renal Disease was found to be <90ml/min in breast cancer 67.8%, colorectal cancer 59.5%, lung cancer 52.6% prostate cancer 62.6% and gynecologic cancer 69.6%. In the study by Yao et al, renal failure rates in cancer patients were found to be 38.2% in uterine cancer, 10.2% in breast cancer, 9.2% in prostate cancer, and 7.2% in liver cancer (16).…”
Section: Discussionmentioning
confidence: 95%
“…Percutaneous nephrostomy was performed in 6.8% of patients with haemodialysis and 6.1% of patients with acute renal failure. The mortality rate in patients with renal insufficiency was 13% (16).…”
Section: Discussionmentioning
confidence: 98%